(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
In the present study, Fe3O4 magnetic nanoparticles (MNPs) synthesized in-housed using co-precipitation method was applied for the treatment of aqueous solutions contaminated by Ni(II) ions. Experimental results indicated that at 25ºC, the optimum pH value for Ni(II) removal was pH 6.0 and an adsorbent dose of 60.0 mg. The adsorption capacity of Fe3O4 nanoparticles for Ni(II) is 20.54 mg g−1. Adsorption kinetic rates were found to be fast; total equilibrium was achieved after 180 min. Kinetic experimental data fitted very well the pseudo-second order equation and the value of adsorption rate constants was calculated to be 0.004 and 0.0008 g mg−1 min at 5 and 40 mg L−1 initial Ni(II) concentrations, respectively. The equilibrium isotherms were evaluated in terms of maximum adsorption capacity and adsorption affinity by the application of Langmuir and Freundlich equations. The maximum monolayer capacity obtained from the Langmuir isotherm was 24.57 mg g−1 for Ni(II). Results indicate that the Langmuir model fits adsorption isotherm data better than the Freundlich model.